Innovative Chemical Engineering Education: Social Media-Enhanced Project-Based Learning Approaches - Diana E. Guaya; Ximena V. Jaramillo-Fierro; Miguel A. Meneses; Eduardo Valarezo (Emerging Science Journal, 2024)
This study investigates the integration of social media platforms, specifically YouTube and TikTok, as educational tools in Project-Based Learning (PBL) within chemical engineering courses, with a particularly focus on Unit Operations. The research involved seventy-eight students from the Universidad Técnica Particular de Loja across two consecutive semesters (April-August 2022 and October 2022-February 2023). Students were tasked with creating educational videos to communicate complex engineering concepts. YouTube was utilized for longer, detailed explanations, while TikTok was employed for short, engaging content. The results demonstrate the effectiveness of this method in enhancing student engagement and comprehension of both theoretical and practical concepts. Instructors observed substantial improvements in student creativity and digital literacy. Quantitative data, such as average course scores, and qualitative feedback from instructors highlight both the strengths and challenges of leveraging social media as a learning tool. A project evaluation rubric was developed to assess performance across several dimensions, including content mastery, practical application, creativity, and engagement. The study concludes that the combination of PBL with social media platforms creates a dynamic, interactive learning environment that cultivates essential skills for future engineers. However, it also identifies areas for refinement, particularly in terms of effective communication through digital media formats. Doi: 10.28991/ESJ-2024-SIED1-021 Full Text: PDF